Argumentação no ensino de ciências da natureza: uma análise dos livros didáticos aprovados pelo PNLD/2021 - Santos, Suellen Fonsêca da Conceição (2024)
This master's thesis aimed to contribute to discussions and studies on argumentation in Biology. This study is structured in multipaper format and encompasses a collection consisting of two articles, the first being theoretical and the next empirical. The present research aims to analyze the development of argumentation in Natural Sciences textbooks considering the limitations and contributions to teaching. It is understood that textbooks that have an argumentative focus are instruments with the potential to contribute to student learning with regard to the development of argumentative skills. In general, this study is based on Toulmin's Argumentation Layout (2006), which is the main theoretical and methodological reference. To develop the first article, we aimed to theoretically discuss the potential of argumentation for teaching Natural Sciences. Scientific argumentation was taken into consideration as a teaching strategy and the role of textbooks in this process. For the development of the empirical article, an analytical tool proposed by Silva (2021), associated with Toulmin's Argumentative Layout (2006), was used as a reference. To this end, the arguments expressed in the statements of Mendel's First Law in High School Natural Sciences textbooks, approved by PNLD/2021, were analyzed. Our analyzes indicate that, for the most part, the arguments about Mendel's First Law recorded in the aforementioned books are not satisfactory. Arguments are considered satisfactory when all elements of an argument fulfill their function, in which, through justifications, a link can be established between the data and a given conclusion (TOUMIN, 2006). In view of these questions, it is relevant that more investigations focused on argumentation in Natural Sciences textbooks are carried out in order to reinforce the existence of this gap and, consequently, the urgency of adapting textbooks to the argumentative context.